2010
DOI: 10.1038/nn.2692
|View full text |Cite
|
Sign up to set email alerts
|

HCN channelopathy in external globus pallidus neurons in models of Parkinson's disease

Abstract: Parkinson’s disease (PD) is a common neurodegenerative disorder characterized by a profound motor disability that is traceable to the emergence of synchronous, rhythmic spiking in neurons of the external segment of the globus pallidus (GPe). The origins of this pathophysiology are poorly defined. Following the induction of a parkinsonian state in mice, there was a progressive decline in autonomous GPe pacemaking that normally serves to desynchronize activity. The loss was attributable to the downregulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
164
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(178 citation statements)
references
References 47 publications
14
164
0
Order By: Relevance
“…We demonstrate that steady-state nanomolar DA enables an activity-dependent mechanism that can contribute to LP phase maintenance by persistently increasing LP I h G max . This mechanism (1) was triggered when there was a prolonged loss of LP network function, (2) may be evolutionarily conserved as loss of dopaminergic tone decreases I h in rhythmically active globus pallidus neurons (Chan et al, 2011), and (3) may represent an adaptation to preserve motor network output with increasing dopaminergic neuronal activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrate that steady-state nanomolar DA enables an activity-dependent mechanism that can contribute to LP phase maintenance by persistently increasing LP I h G max . This mechanism (1) was triggered when there was a prolonged loss of LP network function, (2) may be evolutionarily conserved as loss of dopaminergic tone decreases I h in rhythmically active globus pallidus neurons (Chan et al, 2011), and (3) may represent an adaptation to preserve motor network output with increasing dopaminergic neuronal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Tonic nanomolar DA can act through translation-dependent mechanisms to persistently regulate the voltage-gated transient potassium current (I A ) in an activityindependent fashion (Rodgers et al, 2011). A recent study showed that diminished dopaminergic tone in mouse models of Parkinson's disease caused a loss of pacemaker activity and a reduction in I h in globus pallidus neurons (Chan et al, 2011). Here we used a small motor circuit with well defined neuronal phase relationships underpinned in part, by I A and I h , to examine the long-term effects of steady-state DA on neuronal firing phase.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, studies using healthy rat brain slices described three electrophysiological subgroups of neurons in the GP Stanford, 2000, Bugaysen et al, 2010]. However, other in vitro studies reported no clear qualitative electrophysiological differences amongst GP neurons and challenge the existence of distinct GP neuron types [Chan et al, 2004, Hashimoto and Kita, 2006, Günay et al, 2008, Chan et al, 2011, Deister et al, 2013.…”
Section: Intrinsic Gpe Structurementioning
confidence: 99%
“…Chan et al [2004] proposed HCN channels in GP neuron dendrites as key determinants of regular spiking and synchronization. In a study of HCN channel function in 6-OHDA lesioned mice, Chan et al [2011] uncovered an HCN channelopathy in GP neurons that accompanied pacemaking deficits. HCN channels located presynaptically on GP terminals are known to decrease the likelihood of GABA release [Boyes and Bolam, 2007].…”
Section: Hcn Channel Expressionmentioning
confidence: 99%
See 1 more Smart Citation